Chrésima : Exemplarische Studien zur frühchristlichen Chrêsis - Mülke, Markus (Untersuchungen zur antiken Literatur und Geschichte ;, 2019)
Chrêsis was a critical method used by early Christians to reintegrate ancient cultural products. The chronological and thematic range of the essays collected in this volume demonstrates the fundamental importance and complexity of this method. A study of portraits of bishops from late antiquity from an art historical and archaeological point of view adds insights into the non-literary dimensions of late ancient culture.